Cockpit avionics integration of non-required safety enhancing system installations - Ilinca, A. (My University, 2014)
The airworthiness regulations applicable to systems and installations, not specifically addressed in CS27/29 or FAR27/29, require equipment general installation features e.g. appropriate design, manufacture and installation enabling intended function implementation, avoidance of unacceptable hazard to helicopter due to malfunction or failure. This paper deals with such equipment items, which are not previously ETSO authorized or TSO approved, developed by AH/AHD or AHD suppliers to enhance operational safety. It provides several directions to be followed when new, “non-required” design solutions are proposed to be integrated into the helicopter cockpit design. The discussion is done without addressing a specific system installation; it sums up activities of the applicant’s airworthiness office to support presentation of the design to certification authorities and to propose acceptable means to achieve installation airworthiness approval. The objectives of this paper are to identify features of such “non-required” installation classes to be considered for acceptable cockpit integration. The paper provides overall considerations on certification liaison activities and proposes investigation methods with general applicability. It is not written for a given system architecture and is intended to be a complement for “non-required” system development and integration in helicopter. Its establishment is based on experience gained in the past on AHD experimental projects in which new helicopter functions have been proposed and implemented. Aim of the paper is to discuss airworthiness investigation of installations expected to provide an overall safety benefit, assessing system function development assurance level in combination with integration and compatibility principles. To achieve a large applicability, the paper does not discuss compliance methods which apply to type certification but is reduced to type design changes only.